Modernism—Borders and Crises - Ástráður Eysteinsson (Humanities, 2021)
This article discusses the concept of modernism, as reflected for instance in attempts to find a manageable narrative frame for the history of literary modernism. The article argues that this attempt is complicated by modernism as an unruly and complex trend that manifests itself in different ways, and at different moments, as it enters into a complex dialogue with other trends within various linguistic communities. These different times and places of modernism also turn out to interact with one another through translations and other forms of reception that sometimes entail renewed modernist creativity. Discussing these significant aspects of modernism, the article also considers the problems critics of modernism face as they attempt to come up with a narrative framework for the history of modernism and its ongoing relationship with realism. A key point argued in the article is that to come to terms with both these trends we need to appreciate the ways in which modernism is linked to historical crises and traumas of our time, including the first and the second world wars. Paying particular attention to the interplay of Nordic and European modernisms, the article discusses how aspects of modernism have manifested themselves in Iceland, a Nordic island which may seem doubly removed from the European centres of modernism in cities such as London and Paris.